Morphology of the optic nerve head and factors affecting it in the Northern Finland birth cohort - Pitkänen, J. (Joel); Liinamaa, J. (Johanna); Leiviskä, I. (Ilmari); Saarela, V. (Ville) (John Wiley & Sons, 2023)
Abstract Purpose: To assess topographic characteristics of the optic nerve head (ONH) and retinal nerve fibre layer (RNFL) and study the effect of ocular and physiological factors on them in a middle-aged population. Methods: A 1552-person randomised sample from Northern Finland population aged 45–49 was examined. Laser scanning tomography and optical coherency tomography were performed to obtain measurements for ONH and RNFL morphology. Measurements of the RNFL included global thickness and the six zones used in automated structure–function analysis (S–F analysis). Influence of central corneal thickness (CCT), refractive correction, intraocular pressure (IOP), anterior chamber angle, gender, blood pressure, height, weight and body mass index (BMI) on tomographic data was analysed. Results: The optic disc area had a strong correlation with all other parameters of ONH morphology (R = 0.261 to 0.706) as did spherical equivalent (R = −0.280 to 0.280). The correlations between ONH and RNFL measurements were weaker (R = 0.057 to 0.180). Gender, CCT, anterior chamber angle, blood pressure, height and BMI had statistically significant, yet feeble, correlations with a number of ONH parameters. Conclusion: Other than spherical equivalent, the studied anatomical and physiological attributes had little predictive value on the ONH morphology. The optic disc area itself had a significant effect on other measurements of ONH tomography and should be taken into consideration when the thresholds for normal ONH morphology are calculated.